Prognostic value of sarcopenia in survivors of hematological malignances undergoing a hematopoietic stem cell transplantation: a systematic review and meta-analysis - Jia, Shuli; Qiao, Runjuan; Xiao, Yuting; Qin, Dan; Zhao, Wanyu; Zhao, Yunli; Liu, Xiaolei; Dong, Birong (Supportive care in cancer, 2020)
Purpose Sarcopenia is increasingly recognized as an independent risk factor for poor outcomes in patients undergoing hematopoietic stem cell transplantation (HSCT), and it is a potentially modifiable factor. The purpose of the present systematic review and meta-analysis is to summarize and integrate current evidence in this field. Methods We searched EMBASE, MEDLINE, and Cochrane DSR through Ovid and PubMed websites to identify relevant studies. Studies evaluated sarcopenia before HSCT and reported associations between sarcopenia and post-transplant outcomes were included. Two authors independently applied eligibility criteria, assessed quality, and extracted data. Odds ratio (OR) and their 95% confidence intervals (CIs) were pooled to examine the association between sarcopenia and post-transplant outcomes by using the review manager 5.3 software. Results Seven retrospective cohort studies met our inclusion criteria. The overall quality of studies was low to moderate. Sarcopenia was associated with higher non-relapse mortality [odds ratio (OR) 1.97; 95% CI 1.45, 2.68; P < 0.0001; I 2 = 0%] and shorter overall survival [odds ratio (OR) 0.44; 95% CI 0.26, 0.75; P = 0.002; I 2 = 65%] in patients undergoing HSCT. Conclusions Clinicians could use sarcopenia to balance the risks and benefits of transplantation as early as possible; in addition, interventions can be used to prevent sarcopenia and improve physical function and quality of life. Well-designed, prospective, and large-scale clinical studies are needed to consolidate the evidence.